Natural Compounds as Modulators of NADPH Oxidases. (27th November 2013) - Maraldi, Tullia
Abstract : Reactive oxygen species (ROS) are cellular signals generated ubiquitously by all mammalian cells, but their relative unbalance triggers also diseases through intracellular damage to DNA, RNA, proteins, and lipids. NADPH oxidases (NOX) are the only known enzyme family with the sole function to produce ROS. The NOX physiological functions concern host defence, cellular signaling, regulation of gene expression, and cell differentiation. On the other hand, increased NOX activity contributes to a wide range of pathological processes, including cardiovascular diseases, neurodegeneration, organ failure, and cancer. Therefore targeting these enzymatic ROS sources by natural compounds, without affecting the physiological redox state, may be an important tool. This review summarizes the current state of knowledge of the role of NOX enzymes in physiology and pathology and provides an overview of the currently available NADPH oxidase inhibitors derived from natural extracts such as polyphenols.